RECEPTION ANALYSIS OF RELIGIOUS FIGURES ON DIGITAL DA'WAH BY INDONESIA TANPA PACARAN AND NIKAH INSTITUTE - Zahrotul Farodis Diana (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
Indonesia whitout dating (ITP) is a movement of the dakwah whose vision of removing dating in Indonesia in 2024. But, many peoples and critics who view this movement encourage youth to get an early marriage without preparation. As a result of this unrest, the vision of the Nikah Institute is likely to be able to build a good marriage. The method used is a desktop qualitative research using a Stuart Hall reception analysis. Stuart Hall narrated that reception had attention to analysis in the social and political contexct where media content was produced (encoding), and media content (decoding) in daily living outputs. Stuart Hall divided the reception positions of people in three parts, that are dominant-hegemonic reading, negotiated reading and opositional ‘counter’ hegemonic reading. This research resulted in a finding that one informant occupies a dominant-hegemonic reading position in the ITP da’wah discourse, while the other four occupy a negotiated reading position. It is different with ITP, in understanding and interpreting the Da’wah of Nikah Institute, four informants occupy a dominant-hegemonic reading position, while one informant occupies an negotiated- reading position. From both the discourse of the preaching of ITP and Nikah Institute, there were no informants who held an oppositional-reading position. This shows that ITP and Nikah Institute da’wah discourse can be generally accepted, altough there are some negotiations in interpreting it.